Efforts and Challenges paved by India to confront of Corona Virus (COVID-19) - Khan, Mohammad Gayoor; Yezdani, Umama; Chakravorty, Arghya; Shukla, Tanvi (Bangladesh Journal of Medical Science, 2020)
The clinical range of Covid-19 is a respiratory route infection that varies from Asymptomatic to various clinical conditions such as respiratory failure to multiple organ dysfunction syndromes (MODS). Government administration officials are ramping up many efforts i.e prevention and containing the spread from escalating to the next level, raising the quarantine stations and increase in the laboratory capacity, strengthening surveillance, contact tracing using artificial intelligence (AI) via technology apps. India is Consequently facing many challenges to tackle the pandemic from shortage of medical supply to the devastation of the educational, transportation, job sectors, and healthcare sector, However, pharmaceutical companies taking center stage in the Covid-19 fight, Other pharmaceutical companies(low scale) in India are following suit during the Covid-19 pandemic and using their capabilities to lighten the burden of coronavirus, WHO recommends social distancing and country-wise lockdown are very essential to tackle the coronavirus, the GOI is scheming on how to get back to normalcy, with an actionable exit plan for the states to confront the coronavirus Bangladesh Journal of Medical Science Vol.19(0) 2020 p. S 88-S 92